(untitled) (Bangladesh Journal of Agricultural Research, 2022)
The experiment was conducted to formulate the low calorie cabbage-lime blend Ready-to-Serve (RTS) functional beverage. Considering the results of preliminary studies, six formulations of the low calorie functional RTS beverage were prepared by blending different ratios of cabbage and lime juice (27:3, 24:6, 21:9, 18:12 and 15:15) including control, where only cabbage juice was added. The prepared formulations were subjected to nutritional and sensory evaluation after the formulations were done. Nutritional parameters including titrable acidity, pH, vitamin C, total sugar and total soluble solids were analysed. Sensory attributes of color, aroma, taste, appearance (cloudiness) and overall acceptability were evaluated using a seven point hedonic scale. The nutritional analysis of the fresh low calorie RTS beverage showed the increasing trend in titrable acidity (from 0.32% to 1.3% as citric acid), vitamin C (from 8.35 mg/100 ml to 17.75 mg/100 ml), total sugar (from 2.75% to 4.99%), and total soluble solids (from 4.64 ° Brix to 5.17 °Brix) with the increase of lime juice from 3% to 15%. The pH was reduced when the lime juice concentration increased. The sensory assessment of fresh low calorie RTS beverage revealed that there were significant (p < 0.05) differences among the sensory attributes. The highest overall acceptability was observed in the formulation with 18% cabbage juice and 12% lime juice with ideal functional qualities. Bangladesh J. Agril. Res. 45(2): 157-164, June 2020